2021
DOI: 10.1016/j.xjon.2020.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and immune checkpoint markers are associated with the severity of aortic stenosis

Abstract: Objective: Aortic stenosis (AS) is a disease characterized by narrowing of the aortic valve (AV) orifice. In relation to this disease, the purpose of this study was to elucidate the relationships among factors such as expression of programmed cell death-1 ligand (PD-L1, which is the ligand of PD-1 protein; together, they play a central role in the inhibition of T lymphocyte function), clinicopathologic characteristics, infiltrating immune cells, and disease severity.Methods: We performed immunohistochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Furthermore, PD-L1 protein level was previously shown to be positively associated with aortic valve calcification ( Erkhem-Ochir et al, 2020 ). Here we show that CD274 (encodes PD-L1) was up-regulated with calcification grade in artery tibial and aorta, but not in coronary artery and pituitary.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PD-L1 protein level was previously shown to be positively associated with aortic valve calcification ( Erkhem-Ochir et al, 2020 ). Here we show that CD274 (encodes PD-L1) was up-regulated with calcification grade in artery tibial and aorta, but not in coronary artery and pituitary.…”
Section: Discussionmentioning
confidence: 99%
“…1 The expression of the immune checkpoint protein, programmed cell death 1 protein and its ligand (PD-L1) have been found to inhibit T cell receptor-mediated lymphocyte proliferation and cytokine secretory function. 2 In this issue of the Journal, Erkhem-Ochir and colleagues 3 report the results of an immunohistochemical analysis of aortic valve leaflets in 53 patients undergoing SAVR for severe AS to examine the association of PD-L1 expression and active inflammation in severe calcific AS. PD-L1 expression was significantly associated with infiltration of CD8 þ T lymphocytes and CD163 þ macrophages in aortic leaflet tissue.…”
Section: Harold L Lazar Mdmentioning
confidence: 99%
“…In this issue of the Journal , Erkhem-Ochir and colleagues 3 report the results of an immunohistochemical analysis of aortic valve leaflets in 53 patients undergoing SAVR for severe AS to examine the association of PD-L1 expression and active inflammation in severe calcific AS. PD-L1 expression was significantly associated with infiltration of CD8 + T lymphocytes and CD163 + macrophages in aortic leaflet tissue.…”
mentioning
confidence: 99%
“…In this issue of the Journal , Erkhem-Ochir and colleagues 2 attempted to shed light on the association of immune checkpoint markers with inflammatory infiltration and the progression of calcification of aortic valve leaflets. In their study of surgically resected aortic valve leaflets, they demonstrated an association between high levels of programmed death (PD) ligand 1 (PDL-1) expression, inflammation, and severity of leaflet calcification.…”
mentioning
confidence: 99%